2023
DOI: 10.1093/icvts/ivac291
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic implications of prostaglandin E-major urinary metabolite in resected non-small-cell lung cancer

Abstract: OBJECTIVES Cyclooxygenase-2-derived prostaglandin E2 (PGE2) is highly involved in the promotion of cancer progression. The end product of this pathway, PGE-major urinary metabolite (PGE-MUM), is a stable metabolite of PGE2 that can be assessed non-invasively and repeatedly in urine samples. The aim of this study was to assess the dynamic changes in perioperative PGE-MUM levels and their prognostic significance in non-small-cell lung cancer (NSCLC). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…Therefore, the utility of PGE-MUM is also suggested in conditions related to the COX-2 enzyme, such as lung adenocarcinoma, interstitial pneumonia, and mesenteric adipose inflammation. [23][24][25] In the present study, the SMAO group showed higher PGE-MUM levels than the sham group. Furthermore, even when the duration of reperfusion was the same, the duration of ischemia correlated with higher PGE-MUM levels, suggesting a potential correlation between the degree of intestinal ischemia and PGE-MUM levels independent of reperfusion.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Therefore, the utility of PGE-MUM is also suggested in conditions related to the COX-2 enzyme, such as lung adenocarcinoma, interstitial pneumonia, and mesenteric adipose inflammation. [23][24][25] In the present study, the SMAO group showed higher PGE-MUM levels than the sham group. Furthermore, even when the duration of reperfusion was the same, the duration of ischemia correlated with higher PGE-MUM levels, suggesting a potential correlation between the degree of intestinal ischemia and PGE-MUM levels independent of reperfusion.…”
Section: Discussionsupporting
confidence: 52%
“…Our study showed that intestinal ischemia is associated with PGE-MUM when studied using a rat intestinal ischemia model. Although most reports on PGE-MUM are based on human data, 8,[12][13][14][15][20][21][22][23][24][25] studies to determine the validity of PGE-MUM measurements in rodents after the induction of intestinal ischemia/necrosis are lacking. In the current study, we demonstrated the validity of the PGE-MUM test in rat samples using dilution linearity testing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation